Needs assessment for the development of a college of information and communications technology smart building - Alegado, Rachel T.; Olipas, Cris Norman P.; Carlos, Christine Joyce M. (International Journal of Innovative Research and Scientific Studies, 2025)
This needs assessment aims to evaluate the existing infrastructure and learning environment of the College of Information and Communications Technology (CICT) to determine the necessity and strategic value of developing a CICT Smart Building. The study aligns with the university’s goal of advancing digital transformation and academic excellence through state-of-the-art facilities. This study employed a quantitative descriptive research design to systematically assess the existing infrastructure and gauge demand for innovative learning spaces within CICT. Data were collected from students and faculty through structured online surveys distributed via Google Forms, allowing efficient, cost-effective, and broad participation. The survey focused on current facility utilization, infrastructure challenges affecting learning and research, and preferences for smart building features such as high-performance computing and IoT-enabled classrooms. A convenience sampling method was used to ensure representation across different year levels and faculty groups. Results revealed critical infrastructure deficiencies, including outdated laboratory equipment, overcrowded classrooms, and a lack of collaborative, research-driven, and technology-enhanced spaces. Stakeholders expressed a strong demand for smart classrooms, advanced computing laboratories, multifunction halls, and innovation hubs to support hybrid learning, research activities, and industry collaboration. The findings support the urgent need for a CICT Smart Building. The integration of smart technologies, modern facilities, and collaborative spaces is essential for elevating the quality of instruction, research productivity, and digital readiness of both students and faculty. The proposed development aligns with the university’s Strategic Development Goals (2024–2028). Implementing the CICT Smart Building project will significantly enhance the university’s capacity to deliver innovative, industry-aligned IT and Data Science programs. It will also foster interdisciplinary collaboration and prepare graduates for the demands of the digital economy, positioning the institution as a leader in technology-driven education.